IDENTIFICATION OF DOMINANT FACTORS IN CHOOSING DIPLOMA PROGRAMS IN UNDIKSHA - Marti, Ni Wayan; Jiwa Permana, Agus Aan (Journal of Education Research and Evaluation, 2020)
This study aims to identify the dominant factors related to the interest of prospective students in choosing diploma study programs at the Ganesha Educational University (Undiksha). This research is quantitative descriptive. The method used is a survey method, targeting high school / vocational high school students, and parents of students. Data collection, with the distribution of questionnaires in the region of Buleleng and surrounding areas. There are seven variables used, namely: product, education costs, location, environment, promotion, individual and social economy. The results of the questionnaire were 88 respondents who were high school students, 57 respondents were vocational students, and 68 respondents were parents. Based on the results of data analysis, it was found that the selection of diploma study programs in Undiksha was influenced by several factors such as Products (80.75%), Education (67.29%), Location (68.08%), Environment (41.78% ), Promotion (53.99)%, Individual (65.73%), and Social Economy (78.40%).